(untitled) (Sains Humanika, 2017)
This study intends to examine student achievement in subject of geography. This studyinvolves variables of attitudes, interest, teacherâ€™s role and parentsâ€™ role with student achievement. This is a preliminary study involved only one district in Sabah, Kota Marudu district. Data were collected through a questionnaire which contains 40 items to measure, attitude, interest, teacherâ€™s role and parentsâ€™ roles. Meanwhile, final examination results year 2015 used to measure student achievement for geography subject. A total of 257 Form Five students representing six schools that took geography involved in this study were selected through random sampling. Data were analysed using SPSS software by selecting the Pearson correlation analysis. Research finding showed that studentsâ€™ attitude has a significant relationship with student achievement. Meanwhile, interest, teacherâ€™s roles and parents’ roles have no relationship with student achievement. The findings gave implications for the abolition of geography subjects if student achievement still remained in low-level. Hence, teachers and parents play an important role to form a high interest and a more positive attitude towards students in order to improve their achievement in subject of geography.Â